Analysis of Miller-Seller Curriculum Perspective in Curriculum of Primary School Teacher Education Study Program at Teacher Training and Education College of Weetebula Southwest Sumba East Nusa Tenggara - Agustinus Tanggu Daga (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
This research aims to explain the Miller-Seller curriculum perspective in the curriculum development of the Primary Teacher Education Study Program at STKIP Weetebula. This study is qualitative descriptive research with a literature review method. The results showed that in the curriculum of the PGSD Study Program, there were context, objectives, learning experiences, the role of lecturers, and curriculum evaluation. The curriculum context includes philosophical, psychological, and social. New findings in the curriculum of the PGSD Study Program include, the curriculum context is the philosophy of social reconstruction, humanisti and transpersonal psychology, and local cultural approaches. Learning experiences emphasize inquiry and probem solving, as well as finding the meaning of knowledge. The role of the lecturer as a facilitator of learning, facilitator of finding the meaning of knowledge and skills. Curriculum evaluation emphasizes mastery of learning material, acquisition of problem-solving skills, student self-evaluation. Based on these findings, the authors conclude that in the PGSD Study Program curriculum there is a Miller-Seller curriculum perspective, namely the position of transmission, transaction, and transpersonal. The three curriculum positions have various portions in planning, implementation, and evaluation in the PGSD Study Program curriculum.